Factors Affecting the Complete Response in Breast and Axillary Regions Following Neoadjuvant Chemotherapy for Breast Cancer - Ozgul, Halit; Cakir, Remzi Can; Celik, Omer; Yildiz, Turan Can; Aydemir, Erhan; Hark, Betul Dagoglu; Lale, Azmi (Galenos Publ House, 2024)
Aim: Neoadjuvant chemotherapy (NAC) has transitioned from a treatment modality used solely for inoperable and locally advanced breast cancer to a therapeutic approach for early-stage breast cancer. High-risk patients, such as those with HER2-positive and triple- negative breast cancer, particularly benefit from NAC. This study aimed to evaluate the factors affecting pathological complete response (pCR) in primary breast tumors and axillary lymph nodes in patients with breast cancer. Methods: The study included female patients with breast cancer who received NAC at a training and research hospital between 2020 and 2024. Patients were categorized based on age, tumor stage, and tumor biology: luminal A, HER2-positive luminal B, HER2negative luminal B, HER2-positive alone, or triple-negative. The presence or absence of E-cadherin in tumor cells and Ki-67 levels were also examined. Data were obtained from medical records to assess the impact of these factors on complete response in patients with breast cancer and axillary metastatic lymph nodes following NAC. Results: Univariate analysis revealed that histopathological subtypes, estrogen receptor and progesterone receptor (PR) status, HER2 status, perineural invasion, lymphovascular invasion (LVI), Ki-67 index, and carcinoma in situ (CIS) component significantly influenced pCR. Multivariate analysis confirmed that PR status [Odds ratio (OR): 3.33, 95% confidence interval (CI): 1.57-7.08, p=0.002], HER2 status (OR: 3.56, 95% CI: 1.71-7.44, p=0.001), LVI (OR: 3.91, 95% CI: 1.84-8.30, p<0.001), Ki-67 index (OR: 1.03, 95% CI: 1.01-1.05, p<0.001), and CIS component (OR: 7.01, 95% CI: 2.44-20.11, p<0.001) were independent predictors of complete response. Conclusion: Our findings underscore the multifaceted nature of NAC response in breast cancer, which is influenced by histopathological and molecular characteristics.
Keywords: Neoadjuvant chemotherapy; pathological complete response; breast cancer; axillary lymph nodes